Frequency of Portal Gastropathy in Child Pugh Class A, B, C in Chronic Liver Disease - Aqsa Humayun, Syed Anees Ahmed Gardezi, Najmusaqib Khan Niazi, Syed Haider Tirmizi, Iffat Rafique, Rabia Sadiq, Talha Laique (Pakistan Journal of Medical & Health Sciences, 2022)
Liver disease progresses through four stages of inflammation, fibrosis, cirrhosis leading to hepatocellular carcinoma and liver failure. Aims: To check the frequency of portal gastro-pathy in child Pugh class A, B, C in chronic liver disease. Study Design: Cross sectional study. Methodology: Patients (n=246) with chronic liver disease were included and classified based on the Child-Pugh classification and grouped into category A (good hepatic function), category B (moderately impaired hepatic function and category C (advanced hepatic dysfunction). Findings suggestive of portal gastropathy were noted in the endoscopy reports and were classified as mild or severe according to McCormack criteria. ALT, platelets, Haemoglobin and INR levels were also recorded. Statistical analysis: Data was analyzed using SPSS version 26. Results were presented as frequency and percentage. Age was presented as mean± SD. Results: Out of total 246 patients 155 (63%) were males and 91 (37%) were females. Mean age of the patients was 45.1 ± 10.1 years. 142 (57.7%) patients were of child PUGH class A, 66 (26.8%) were of class B and 38 (15.4%) were of class C. Frequency of portal gastropathy was 62.2% (n=153). In our study 57.7% patients in child PUGH class A, 69.6% of Child PUGH class B and 65.7% in PUGH class C were positive with PHG findings. Conclusion: It was concluded that Portal hypertensive gastropathy was not significantly related to the Child Pugh classification of liver disease. However, an increase in ALT levels depicted the severity of liver damage.